Viscoelastic behaviors of hyaluronic derivatives as a function of pH, salt, and temperature - Kadam, Yogesh; Badiger, Manohar V.; Rajamohanan, Pattuparambil R.; Wadgaonkar, Prakash P.; Ducouret, Guylaine; Merland, Theo; Hourdet, Dominique (Journal of Polymer Science, 2026)
Hyaluronic acid and its derivatives are essential polysaccharides widely used in the bio-medical field for their applications in tissue engineering and controlled drug delivery. By revisiting the wide variety of rheological behavior of aqueous hyaluronan solutions as a function of pH, we develop in this work a comparative study between solutions of native hyaluronan (HA) and its derivative (HA-PEPO) obtained by grafting onto thermoresponsive side-chains of poly(ethylene oxide-co-propylene oxide) characterized by a phase transition around body temperature. Based on a large dataset obtained at a fixed polymer concentration, by changing either the chemical composition of the chain and/or the environmental conditions (pH, temperature, added salt), we show that the viscoelastic properties of hyaluronan solutions can be controlled over more than three decades of amplitude with the possibility to get either liquid or gel states, regardless of temperature, as well as sol/gel transitions induced by cooling or heating by the interplay between hydrogen bonds, hydrophobic interactions, and cation binding induced by potassium salts.
Keywords: hyaluronan; Hydrogel; pH-induced gelation; salt-induced gelation; thermoresponsive polymers; tissue engineering